Bioinspired coupled helical coils for soft tissue engineering of tubular structures – Improved mechanical behavior of tubular collagen type I templates. (1st September 2017) - Janke, H.P.; Bohlin, J.; Lomme, R.M.L.M.; Mihaila, S.M.; Hilborn, J.; Feitz, W.F.J.; Oosterwijk, E.
Graphical abstract: Abstract: The design of constructs for tubular tissue engineering is challenging. Most biomaterials need to be reinforced with supporting structures such as knittings, meshes or electrospun material to comply with the mechanical demands of native tissues. In this study, coupled helical coils (CHCs) were manufactured to mimic collagen fiber orientation as found in nature. Monofilaments of different commercially available biodegradable polymers were wound and subsequently fused, resulting in right-handed and left-handed polymer helices fused together in joints where the filaments cross. CHCs of different polymer composition were tested to determine the tensile strength, strain recovery, hysteresis, compressive strength and degradation of CHCs of different composition. Subsequently, seamless and stable hybrid constructs consisting of PDSII® USP 2-0 CHCs embedded in porous collagen type I were produced. Compared to collagen alone, this hybrid showed superior strain recovery (93.5 ± 0.9% vs 71.1 ± 12.6% in longitudinal direction; 87.1 ± 6.6% vs 57.2 ± 4.6% in circumferential direction) and hysteresis (18.9 ± 2.7% vs 51.1 ± 12.0% in longitudinal direction; 11.5 ± 4.6% vs 46.3 ± 6.3% in circumferential direction). Furthermore, this hybrid construct showed an improved Young's modulus in both longitudinal (0.5 ± 0.1 MPa vs 0.2 ± 0.1 MPa; 2.5-fold) and circumferential (1.65 ± 0.07 MPa vs (2.9 ± 0.3) × 10 −2  MPa; 57-fold) direction, respectively, compared to templates created from collagen alone. Moreover, hybrid template characteristics could be modified by changing the CHC composition and CHCs were produced showing a mechanical behavior similar to the native ureter. CHC-enforced templates, which are easily tunable to meet different demands may be promising for tubular tissue engineering. Statement of Significance: Most tubular constructs lack sufficient strength and tunability to comply with the mechanical demands of native tissues. Therefore, we embedded coupled helical coils (CHCs) produced from biodegradable polymers – to mimic collagen fiber orientation as found in nature – in collagen type I sponges. We show that the mechanical behavior of CHCs is very similar to native tissue and strengths structurally weak tubular constructs. The production procedure is relatively easy, reproducible and mechanical features can be controlled to meet different mechanical demands. This is promising in template manufacture, hence offering new opportunities in tissue engineering of tubular organs and preventing graft failure.